2021
DOI: 10.1002/dvg.23419
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a new mouse line with conditionally activated signaling through the BMP receptor, ACVR1: A tool to characterize pleiotropic roles of BMP functions

Abstract: BMP signaling plays pleiotropic roles in various tissues during embryogenesis and after birth. We have previously generated a constitutively activated Acvr1(ca-Acvr1) transgenic mouse line (line L35) through pronuclei injection to investigate impacts of enhanced BMP signaling in a tissue specific manner. However, line L35 shows a restricted expression pattern of the transgene. Here, we generated another ca-Acvr1 transgenic line, line A11, using embryonic stem (ES) transgenesis. The generated line A11 shows dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…There are still questions why three transgenic mice, i.e., caBmpr1a mice, caAcvr1-L35 mice, and caAcvr1-A11 mice crossed with P0-Cre mice, showed different phenotypes. We found that the phosphorylation level of SMAD1/5/9 differs between caAcvr1-L35 mice and caAcvr1-A11 mice ( Yang et al, 2021b ), which may be a reason for similar but distinct phenotypes between these two lines. Another possibility is that because these mice have been generated through random transgenesis, their expression patterns may be different depending on the genomic locus where the transgenic constructs are integrated.…”
Section: Orofacial Cleftmentioning
confidence: 76%
See 1 more Smart Citation
“…There are still questions why three transgenic mice, i.e., caBmpr1a mice, caAcvr1-L35 mice, and caAcvr1-A11 mice crossed with P0-Cre mice, showed different phenotypes. We found that the phosphorylation level of SMAD1/5/9 differs between caAcvr1-L35 mice and caAcvr1-A11 mice ( Yang et al, 2021b ), which may be a reason for similar but distinct phenotypes between these two lines. Another possibility is that because these mice have been generated through random transgenesis, their expression patterns may be different depending on the genomic locus where the transgenic constructs are integrated.…”
Section: Orofacial Cleftmentioning
confidence: 76%
“…Although the phenotype differences between us and other laboratories might be developed by the difference of Wnt1-Cre mice and P0-Cre mice, it is reasonable to speculate that unbalance between the SMAD-dependent and SMAD-independent pathways in cranial NCCs may be a reason for an orofacial cleft in P0-Cre;caBmpr1a fl/+ ;Tak1 fl/fl mice. We recently reported that two transgenic mouse lines expressing constitutively activated Acvr1 ( caAcvr1 , Acvr1 with the Q207D mutation) in NCCs in mice ( P0-Cre;caAcvr1-L35 line and P0-Cre;caAcvr1-A11 line ) develops midfacial defects including orofacial cleft ( Yang et al, 2021a ; Yang et al, 2021b ). Interestingly, the facial phenotypes between P0-Cre;caAcvr1-L35 line and P0-Cre;caAcvr1-A11 line are different.…”
Section: Orofacial Cleftmentioning
confidence: 99%
“…While the expression of constitutively activated Bmpr1a in CNCCs did not affect overt midfacial structures (24)(25)(26), we sought to define the in vivo impact of increased BMP/Smad signaling via ACVR1, another type I BMP receptor, on midfacial morphogenesis. To this end, we generated a transgenic mouse model with a floxed constitutively activated Acvr1 allele (line A11, ca-Acvr1(A11)) (27) and crossed it with P0-Cre (28) to enhance BMP/Smad signaling in a neural crest-specific manner. Unexpectedly, we found that over 85% of the ca-Acvr1(A11) mutants (ca-Acvr1(A11) fl/+ ;P0-Cre) displayed drastic midline facial defects, including a midline facial cleft, missing primary palate, bifurcated nasal septum, and short snout (Figure 1, B and C, and Supplemental Figure 1, A-C; supplemental material available online with this article; https://doi.org/10.1172/JCI165787DS1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to craniofacial morphogenesis, defects were identified in other NCC-derived tissues in ca-Acvr1(A11) mutants, such as in cardiac neural crest-derived tissues of the heart (27) and trunk neural crest-derived dorsal root ganglion (DRG) of the peripheral nervous system in association with elevated pSmad1/5/9 and cell death (Supplemental Figure 8, A-D). Similarly, elevated BMP signaling downregulated the histone lactylation and PDGFRA expression in cardiac and trunk neural crest derivatives in vivo (Supplemental Figure 8, E and F).…”
Section: Bmp-mediated Regulation Of Pdgfra Histone Lactylation Direct...mentioning
confidence: 99%
“…8). Transgenic mice are often used to investigate the role of a gene in palate development by altering its expression at specific time points and tissues [36][37][38] . Therefore, the study of the time and site of OCL differentiation in embryonic palatal bone can be the basis for further research.…”
Section: Discussionmentioning
confidence: 99%